MPA-modified CdTe quantum dots increased interleukin-1beta secretion through MyD88-dependent Toll-like receptor pathway and NLRP3 inflammasome activation in microglia. (October 2018) - Wu, Tianshu; Liang, Xue; He, Keyu; Wei, Tingting; Wang, Yan; Lu, Jie; Yao, Ying; Zhang, Ting; Xue, Yuying; Tang, Meng
Abstract: The excellent optical properties of CdTe quantum dots (QDs) make researchers realize their value on the application of biomedicine, especially neuroscience, as an advanced fluorescent probe. Thus, it is important to evaluate the biosafety of CdTe QDs on the central nervous system (CNS). Our previous studies have conducted a systematic biosafety evaluation of CdTe QDs on the CNS and found several toxic endpoints, one of which is the inflammation on the rat hippocampus, but their underlying mechanism remains unclear. In this study, when BV2 microglial cells were exposed to CdTe QDs with doses <20 nM, there was no obviously adverse effect. However, 40 nM CdTe QDs exposure could significantly activate the BV2 cells and increase the pro-inflammatory cytokine IL-1ß secretion. Molecular biology analyses suggested that both TLR2/MyD88/NF-κB pathway and NLRP3 inflammasome participated in the CdTe QD-induced IL-1ß secretion. The former served as the first signal for pro-IL-1ß expression, while the later played a role on the maturation of pro-IL-1ß into IL-1ß. The results, taken together, demonstrated that MPA-modified CdTe QDs exposure with a high concentration was capable of activating microglial cells and promoting IL-1ß secretion, which was highly correlated with the activations of both TLR2/MyD88/NF-κB pathway and ROS-induced NLRP3 inflammasome. These findings provide some mechanistic insights regarding the neuroinflammatory responses to cadmium-based QDs. Graphical abstract: Highlights: Cadmium-based quantum dots (QDs) have value in the biomedical applications. CdTe QDs activated microglial cells and increased interleukin-1ß (IL-1ß) secretion. The expression of pro-IL-1ß increased in CdTe QD-treated cells because of the nuclear factor κB (NF-κB) activation. CdTe QDs caused excessive ROS generation to trigger NLRP3 inflammasome activation.